Exploring the extracellular matrix in health and disease using proteomics. Issue 3 (28th August 2019) - Taha, Isra N.; Naba, Alexandra
Abstract : The extracellular matrix (ECM) is a complex assembly of hundreds of proteins that constitutes the scaffold of multicellular organisms. In addition to providing architectural and mechanical support to the surrounding cells, it conveys biochemical signals that regulate cellular processes including proliferation and survival, fate determination, and cell migration. Defects in ECM protein assembly, decreased ECM protein production or, on the contrary, excessive ECM accumulation, have been linked to many pathologies including cardiovascular and skeletal diseases, cancers, and fibrosis. The ECM thus represents a potential reservoir of prognostic biomarkers and therapeutic targets. However, our understanding of the global protein composition of the ECM and how it changes during pathological processes has remained limited until recently. In this mini-review, we provide an overview of the latest methodological advances in sample preparation and mass spectrometry-based proteomics that have permitted the profiling of the ECM of now dozens of normal and diseased tissues, including tumors and fibrotic lesions.